DIGITAL ACCOUNTING FOR THE NEXT FUTURE: STIMULUS, TRANSITION AND JOURNEYS - Kamkankaew, Pongsiri; Tantavichet, Darinee; Churimas, Siriphan; Limphothong, Sukrit; Phattarowas, Vachiraporn; Khumwongpin, Surakit; Sanpatanon, Nateetip (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2022)
As part of the transition to the digital age, accounting has both a substantial role and a responsibility to society, the importance of which is divided between the legal obligation and the managerial obligation. Consequently, the goal of this academic research was to assess the impact of the accountant and technological advancements on the transition to digital accounting. In order to meet the goal of this paper, interpretative methods were employed to obtain data from a review of the relevant literature. According to the debate in this paper, it is decided that the time accountants spend in their everyday work environments providing services necessitates a transformation. Regarding the influence and evolution of automatisms in the profession, the positive effects of automatisms are evident, disproving the idea that the transition to digital accounting poses a threat to the survival of the accounting profession. This article's findings imply that accountants will be able to enter different industries, fostering their intellectual and personal growth. In this way, accounting can continue to show how important it is to society and become an even more respected job.